1991
DOI: 10.1515/znc-1991-3-408
|View full text |Cite
|
Sign up to set email alerts
|

Marine Biosurfactants, II. Production and Characterization of an Anionic Trehalose Tetraester from the Marine Bacterium Arthrobacter sp. EK 1

Abstract: Within a screening for biosurfactants we could isolate various n-alkanes utilizing marine bacteria which were capable of synthesizing glycolipids. One strain was identified as Arthrobacter sp. EK 1 which produced trehalose lipids. After purification by column and thick layer chromatography the main fraction, an anionic 2,3,4,2′-trehalose tetraester, was obtained. The chain lengths of fatty acids ranged from 8 up to 14, furthermore succinate could be detected. Since the place of substitution of succinate has so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…strain EK1. In this tetraester, trehalose was found to be esterified at C-2 position with succinate (Passeri et al, 1991). R. erythropolis strain SD74 grown on n-hexadecane excreted two other trehalose tetraesters, 2,3,4,29-di-O-succinoyl-di-O-alkanoyl-a,atrehalose and 2,3,4-mono-O-succinoyl-di-O-alkanoyl-a,atrehalose.…”
Section: Discussionmentioning
confidence: 99%
“…strain EK1. In this tetraester, trehalose was found to be esterified at C-2 position with succinate (Passeri et al, 1991). R. erythropolis strain SD74 grown on n-hexadecane excreted two other trehalose tetraesters, 2,3,4,29-di-O-succinoyl-di-O-alkanoyl-a,atrehalose and 2,3,4-mono-O-succinoyl-di-O-alkanoyl-a,atrehalose.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been found that indeed, RLs promote the uptake and biodegradation of poorly soluble substrates. Although most of the literature is concerned with the conversion of hydrocarbons and vegetable oils as substrates for production (Syldatk et al 1985;Passeri et al 1991;Lang and Wullbrandt 1999) water-miscible substrates, such as glucose or other carbohydrates have also been used (GuerraSantos et al 1984;Spoecker et al 1999). The production of extracellular RLs by P. aeruginosa is strictly regulated and maximal RLs synthesis is found under conditions of nitrogen limitation during the stationary phase of growth, using glucose, glycerol, or n-paraffins as carbon sources (Mulligan and Gibbs 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, biosurfactants are not only produced by micro‐organisms growing in water‐immiscible substrates, although most of the literature is concerned with the conversion of hydrocarbons and vegetable oils as substrates for production ( Syldatk et al . 1984 ; Passeri et al . 1991 ; Lang & Wullbrandt 1999).…”
mentioning
confidence: 99%